Reference values and prediction equations for normal lung function in a non-smoking white urban population. Issue 9 (September 1991) - Roberts, C M; MacRae, K D; Winning, A J; Adams, L; Seed, W A
Abstract : Prediction equations for normal lung function have been derived from tests on 179 healthy, non-smoking, white urban dwellers. The subjects, 96 women (height 1.46-1.77 m) and 83 men (height 1.61-1.96 m) aged 18-86 years, underwent measurements of spirometric flow and volume, multi-breath helium dilution lung volumes, and single breath carbon monoxide transfer factor and the single breath nitrogen washout test. Regression analysis using height, age, and weight as independent variables was used to provide predicted values for both sexes. Correlation coefficients were similar to those found in previous studies but normal ranges for spirometic measurements were narrower than in many previous studies, and spirometric flow and volume measurements were higher than those obtained in studies that included cigarette smokers, reflecting our more stringent criteria for selecting subjects and the newer standardised technical methods adopted. Multi-breath helium dilution values for total lung capacity were similar to those found in previous studies but the inspiratory vital capacity was larger and the residual volume reduced. Values for carbon monoxide transfer factor and the single breath nitrogen washout did not differ significantly from existing values. A complete set of lung function reference values and prediction equations for both sexes has been derived from a single population. The exclusion of cigarette smokers and subjects with respiratory symptoms has produced values that should have a greater sensitivity in the detection of mild lung disease.